Taxonomic Diversity of Fungi Associated with Some PCN Populations from Serbia - Oro, Violeta M (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Increased content of pesticides in food chain resulted in using microorganisms as agents of biological control. The potato cyst nematodes (PCN) - Globodera pallida and G. rostochiensis belong to the group of the most important parasites - the quarantine organisms. The external and internal area of a cyst harbor numerous fungal and bacterial species. The aim of this study was to identify antagonistic fungi associated with some PCN populations from Serbia. Fungal antagonists of potato cyst nematodes have not been previously investigated in our country. The diversity of PCN fungal antagonists is not reflected only at the species level but also at the level of higher taxonomic categories.